A Study on Primary Sources of Job Stress Among Government Administrative Staff - Fasina, M.; Sudha , Dr.V. (International Journal of Accounting and Economics Studies, 2025)
Government administrative staff face major issues with workplace stress due to stress stressful nature of their work, high public expectations, and organizational stress. This study investigates the leading causes of stress at jobs related to government employees and assesses the effectiveness of methods and techniques of coping with stress. According to the analysis, the most problematic stressors for the employees are the high pressure of public service duties, precariousness of the job, and lack of career evolution. Other contributing factors to increased stress levels are interpersonal conflicts, work-life imbalance, and heavy workloads with strict deadlines. The variation on the impact of such stressors is confirmed to be statistically significant by a Friedman Test, thus calling for targeted interventions for each issue. The study explores how coping with various techniques presents some of the most effective ways to reduce stress, as shown by ANOVA results, such as being involved in physical activities and wellness programs, taking part in stress management programs led by leaders, and having work flexibility. Other fruitful approaches, such as continuous skill development and prioritized work, add to employee resilience and satisfaction on the job. Based on the findings, structured support systems, proactive leader engagement, and adaptive workplace policies will be needed to help shape a healthier and more productive work environment. In government administrative settings, these measures can be implemented and can greatly contribute to the well-being of employees, lowering workplace stress and increasing the total efficiency of the organization.